Accelerated 1H MRSI using randomly undersampled spiral‐based k‐space trajectories. Issue 1 (30th July 2014) - Chatnuntawech, Itthi; Gagoski, Borjan; Bilgic, Berkin; Cauley, Stephen F.; Setsompop, Kawin; Adalsteinsson, Elfar
<x xml:space="preserve">Abstract</x> Purpose To develop and evaluate the performance of an acquisition and reconstruction method for accelerated MR spectroscopic imaging (MRSI) through undersampling of spiral trajectories. Theory and Methods A randomly undersampled spiral acquisition and sensitivity encoding (SENSE) with total variation (TV) regularization, random SENSE+TV, is developed and evaluated on single‐slice numerical phantom, in vivo single‐slice MRSI, and in vivo three‐dimensional (3D)‐MRSI at 3 Tesla. Random SENSE+TV was compared with five alternative methods for accelerated MRSI. Results For the in vivo single‐slice MRSI, random SENSE+TV yields up to 2.7 and 2 times reduction in root‐mean‐square error (RMSE) of reconstructed N‐acetyl aspartate (NAA), creatine, and choline maps, compared with the denoised fully sampled and uniformly undersampled SENSE+TV methods with the same acquisition time, respectively. For the in vivo 3D‐MRSI, random SENSE+TV yields up to 1.6 times reduction in RMSE, compared with uniform SENSE+TV. Furthermore, by using random SENSE+TV, we have demonstrated on the in vivo single‐slice and 3D‐MRSI that acceleration factors of 4.5 and 4 are achievable with the same quality as the fully sampled data, as measured by RMSE of reconstructed NAA map, respectively. Conclusion With the same scan time, random SENSE+TV yields lower RMSEs of metabolite maps than other methods evaluated. Random SENSE+TV achieves up to 4.5‐fold acceleration with comparable data quality as the fully sampled acquisition. Magn Reson Med 74:13–24, 2015. © 2014 Wiley Periodicals, Inc.